Relasi Sosial Etnis Tionghoa dan Pribumi di Pasar Lama Kota Tangerang - Niken Utami; Haryono Haryono; Wahid Abdul Kudus (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Social life of a diverse society requires a sense of respect to different customs, customs, religion or anything else, so that a shared identity is created in which good relations are established between members of community. Society must be able to understand different characteristics of existing phenomena as a means of maintaining relationships and minimizing conflict. This research describes the social relations of Chinese and Indigenous communities in Pasar Lama, Tangerang City. This research uses a qualitative approach with descriptive methods. Data collection was carried out through interviews, observation and documentation. The informants in this research were Chinese and Indigenous people in Pasar Lama, Sukasari Village, Tangerang City selected based on purposive techniques. Data validity was checked using source and technical triangulations and then analyzed using data reduction, data presentation and conclusion drawing. The theory used is Stafford and Canary's Relational Maintenance Theory consisting of positivity, openness, assurances, sharing tasks, and social networks. The result of research show that the openness of interaction between Chinese and Indigenous communities has been going on for a relatively long time, and finally being able to create adjustments amidst differences in culture, religion, traditions and habits. Positivity manifested in Chinese and Indigenous people’s open attitude in Pasar Lama was ultimately able to create positive relationships, influence each other and work well because of the tolerance between the two groups so that conflict could be minimized. Security (guaranty) appears in personal social relationships, namely marriage between Chinese and Native couples. Task Division is manifested into individual participation in various social activities such as mutual cooperation, community service, or national holiday activities. Social networks can be seen in open interactions leading to the formation of unity between them, creating relationships that occur in all aspects of life, including social, cultural, economic and educational. The conclusion drawn is that relationship maintenance strategies are related to social relations that occur between individuals or groups. Relationship maintenance strategies are effective for maintaining and developing positive and stable relationships in people's lives.